The evolution of British immigrant integration policy after World War II: a historical and political science perspective - Kurcewicz, Urszula (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The paper presents the evolution of the British model of immigrant integration after World War II. It is a historical and political analysis. The author indicates the key elements of the British approach to decolonisation which were translated into concrete legal acts regulating the lives of the Commonwealth residents and immigrants arriving in the UK. The paper also discusses different dimensions of the integration of immigrants into British society. The analysis indicates that the multicultural model of immigrant integration adopted after World War II has been found to be dysfunctional, as British society has reached a state of super-diversity, becoming a very complex mosaic of races, religions and nationalities.

W artykule ukazana została ewolucja brytyjskiego modelu integracji imigrantów po II wojnie światowej. Artykuł stanowi analizę historyczno-politologiczną. Autorka wskazuje kluczowe elementy brytyjskiego podejścia do procesu dekolonizacji, które przełożyły się na konkretne regulacje prawne odnoszące się do mieszkańców Commonwealthu i imigrantów napływających do Wielkiej Brytanii. W artykule omówione zostały również płaszczyzny integracji imigrantów ze społeczeństwem brytyjskim. Analiza wskazuje, iż przyjęty po II wojnie światowej multikulturowy model integracji imigrantów został zakwestionowany jako dysfunkcyjny w obliczu osiągnięcia przez brytyjskie społeczeństwo stadium nad różnorodności (super-diversity), czyli bardzo skomplikowanej mozaiki ras, religii i narodowości.
Ewolucja brytyjskiej polityki integracji imigrantów po II wojnie światowej: perspektywa historyczno-politologiczna
Keywords: migration; Great Britain; integration model; immigrant; migracja; Wielka Brytania; model integracji; imigrant